A study on the inhibitory mechanism for cholesterol absorption by α-cyclodextrin administration - Furune, Takahiro; Ikuta, Naoko; Ishida, Yoshiyuki; Okamoto, Hinako; Nakata, Daisuke; Terao, Keiji; Sakamoto, Norihiro (Beilstein Journal of Organic Chemistry, 2014)
Background: Micelle formation of cholesterol with lecithin and bile salts is a key process for intestinal absorption of lipids. Some dietary fibers commonly used to reduce the lipid content in the body are thought to inhibit lipid absorption by binding to bile salts and decreasing the lipid solubility. Amongst these, α-cyclodextrin (α-CD) is reportedly one of the most powerful dietary fibers for decreasing blood cholesterol. However, it is difficult to believe that α-CD directly removes cholesterol because it has a very low affinity for cholesterol and its mechanism of action is less well understood than those of other dietary fibers. To identify this mechanism, we investigated the interaction of α-CD with lecithin and bile salts, which are essential components for the dissolution of cholesterol in the small intestine, and the effect of α-CD on micellar solubility of cholesterol.Results: α-CD was added to Fed-State Simulated Intestinal Fluid (FeSSIF), and precipitation of a white solid was observed. Analytical data showed that the precipitate was a lecithin and α-CD complex with a molar ratio of 1:4 or 1:5. The micellar solubility of cholesterol in the mixture of FeSSIF and α-CD was investigated, and found to decrease through lecithin precipitation caused by the addition of α-CD, in a dose-dependent manner. Furthermore, each of several other water-soluble dietary fibers was added to the FeSSIF, and no precipitate was generated.Conclusion: This study suggests that α-CD decreases the micellar solubility of cholesterol in the lumen of the small intestine via the precipitation of lecithin from bile salt micelles by complex formation with α-CD. It further indicates that the lecithin precipitation effect on the bile salt micelles by α-CD addition clearly differs from addition of other water-soluble dietary fibers. The decrease in micellar cholesterol solubility in the FeSSIF was the strongest with α-CD addition.
Keywords: α-cyclodextrin; bile salt micelles; cholesterol; lecithin; micellar solubility

Cyclodextrin Technology - Szejtli, J. (Kluwer Academic Publishers, 1988)

(untitled) - Schlenk, H.; Sand, D. M. (J. Am. Chem. Soc., 1961)

(untitled) - Kashino, E.; Fujii, T. (Nihon Kasei Gakkai shi, 2005)

(untitled) - Reineccius, T. A.; Reineccius, G. A.; Peppard, T. L. (J. Food Sci., 2002)

(untitled) - Holm, R.; Schönbeck, C.; Askjær, S.; Jensen, H.; Westh, P.; Østergaard, J. (J. Sep. Sci., 2011)

(untitled) - Hădărugă, N. G.; Hădărugă, D. I.; Păunescu, V.; Tatu, C.; Ordodi, V. L.; Bandur, G.; Lupea, A. X. (Food Chem., 2006)

(untitled) - Duchêne, D.; Bochot, A.; Yu, S.-C.; Pépin, C.; Seiller, M. (Int. J. Pharm., 2003)

(untitled) - Inoue, M.; Hashizaki, K.; Taguchi, H.; Saito, Y. (J. Oleo Sci., 2009)

(untitled) - Artiss, J. D.; Brogan, K.; Brucal, M.; Moghaddam, M.; Jen, K.-L. C. (Metabolism, 2006)

(untitled) - Grunberger, G.; Jen, K.-L. C.; Artiss, J. D. (Diabetes/Metab. Res. Rev., 2007)

(untitled) - Comerford, K. B.; Artiss, J. D.; Jen, K.-L. C.; Karakas, S. E. (Obesity, 2011)

(untitled) - Jen, K.-L. C.; Grunberger, G.; Artiss, J. D. (Nutr. Diet. Suppl., 2013)

(untitled) - Wagner, E. M.; Jen, K.-L. C.; Artiss, J. D.; Remaley, A. T. (Metab., Clin. Exp., 2008)

(untitled) - Buckley, J. D.; Thorp, A. A.; Murphy, K. J.; Howe, P. R. C. (Ann. Nutr. Metab., 2006)

(untitled) - Jarosz, P. A.; Fletcher, E.; Elserafy, E.; Artiss, J. D.; Jen, K.-L. C. (Metabolism, 2013)

(untitled) - Kaewprasert, S.; Okada, M.; Aoyama, Y. (J. Nutr. Sci. Vitaminol., 2001)

(untitled) - Nakanishi, K.; Nakata, D.; Konishi, M.; Uekaji, Y.; Terao, K. (J. Inclusion Phenom. Macrocyclic Chem., 2007)

(untitled) - De Bie, A. T. H. J.; Van Ommen, B.; Bär, A. (Regul. Toxicol. Pharmacol., 1998)

(untitled) - Mueller, K. (Biochemistry, 1981)

(untitled) - Mazer, N. A.; Carey, M. C.; Kwasnick, R.; Benedek, G. B. (Biochemistry, 1979)

(untitled) - Mazer, N. A.; Benedek, G. B.; Carey, M. C. (Biochemistry, 1980)

(untitled) - Porter, C. J. H.; Trevaskis, N. L.; Charman, W. N. (Nat. Rev. Drug Discovery, 2007)

(untitled) - Ikeda, I.; Imasato, Y.; Sasaki, E.; Nakayama, M.; Nagao, H.; Takeo, T.; Yayabe, F.; Sugano, M. (Biochim. Biophys. Acta, 1992)

(untitled) - Abadie, C.; Hug, M.; Kübli, C.; Gains, N. (Biochem. J., 1994)

(untitled) - Cabrer, P. R.; Álvarez-Parrilla, E.; Al-Soufi, W.; Meijide, F.; Rodriguez Núñeza, E.; Vázquez Tato, J. (Supramol. Chem., 2003)

(untitled) - Ohtani, Y.; Irie, T.; Uekama, K.; Fukunaga, K.; Pitha, J. (Eur. J. Biochem., 1989)

(untitled) - Fauvelle, F.; Debouzy, J. C.; Crouzy, S.; Göschl, M.; Chapron, Y. (J. Pharm. Sci., 1997)

(untitled) - Debouzy, J. C.; Fauvelle, F.; Crouzy, S.; Girault, L.; Chapron, Y.; Göschl, M.; Gadelle, A. (J. Pharm. Sci., 1998)

(untitled) - Miyajima, K.; Saito, H.; Nakagaki, M. (Nippon Kagaku Kaishi, 1987)

(untitled) - Motoyama, K.; Arima, H.; Toyodome, H.; Irie, T.; Hirayama, F.; Uekama, K. (Eur. J. Pharm. Sci., 2006)

(untitled) - Vertzoni, M.; Fotaki, N.; Nicolaides, E.; Reppas, C.; Kostewicz, E.; Stippler, E.; Leuner, C.; Dressman, J. (J. Pharm. Pharmacol., 2004)

(untitled) - Lungberg, B. (Acta Chem. Scand., 1973)

(untitled) - Kobayashi, M.; Nishizawa, M.; Inoue, N.; Hosoya, T.; Yoshida, M.; Ukawa, Y.; Sagesaka, Y. M.; Doi, T.; Nakayama, T.; Kumazawa, S.; Ikeda, I. (J. Agric. Food Chem., 2014)

(untitled) - Fromm, H.; Amin, P.; Klein, H.; Kupke, I. (J. Lipid Res., 1980)

(untitled) - Kondo, S.; Xiao Shimizu, J. Z.; Miyaji, K.; Iwatsuki, K.; Ebihara, K. (J. Jpn. Soc. Nutr. Food Sci., 2007)

(untitled) - Minekus, M.; Jelier, M.; Xiao, J.-Z.; Kondo, S.; Iwatsuki, K.; Kokubo, S.; Bos, M.; Dunnewind, B.; Havenaar, R. (Biosci., Biotechnol., Biochem., 2005)

(untitled) - Kishimoto, Y.; Oga, H.; Tagami, H.; Okuma, K.; Gordon, D. T. (Eur. J. Nutr., 2007)

(untitled) - Kishimoto, Y.; Yoshikawa, Y.; Miyazato, S.; Oga, H.; Yamada, T.; Tagami, H.; Hashizume, C.; Yamamoto, K. (J. Health Sci., 2009)

(untitled) - Causey, J. L.; Feirtag, J. M.; Gallaher, D. D.; Tungland, B. C.; Slavin, J. L. (Nutr. Res., 2000)

(untitled) - Ogata, S.-I.; Fujimoto, K.; Iwakiri, R.; Matsunaga, C.; Ogawa, Y.; Koyama, T.; Sakai, T. (Proc. Soc. Exp. Biol. Med., 1997)

(untitled) - Vahouny, G. V.; Roy, T.; Gallo, L. L.; Story, J. A.; Kritchevsky, D.; Cassidy, M.; Grund, B. M.; Treadwell, C. R. (Am. J. Clin. Nutr., 1978)

(untitled) - Shaw, R.; Elliott, W. H. (Lipids, 1978)

(untitled) - Zhang, R.-Z.; Li, L.; Liu, S.-T.; Chen, R.-M.; Rao, P.-F. (J. Food Biochem., 1999)